Little sister : my investigation into the mysterious death of Natalie Wood - Wood, Lana, 1946-; Harrison, Lindsay (Dey St., an imprint of William Morrow, 2021)
In this true crime memoir, the author presents a candid account of the life and death of her sister, revealing decades-old secrets and setting the record straight on one of Hollywood's most notorious celebrity deaths.